Closely related species differ in their traits, but competition induces high intra-specific variability - Janíková, Eva; Konečná, Marie; Lisner, Aleš; Applová, Markéta; Blažek, Petr; E-Vojtkó, Anna; Götzenberger, Lars; Lepš, Jan (Ecology and evolution, 2024)
Theories explaining community assembly assume that biotic and abiotic filters sort species into communities based on the values of their traits and are thus based on between-species trait variability (BTV). Nevertheless, these filters act on individuals rather than on species. Consequently, the selection is also influenced by intraspecific trait variability (ITV) and its drivers. These drivers may be abiotic (e.g., water availability) or biotic (e.g., competition). Although closely related species should have similar traits, many of them coexist. We investigated the relative magnitudes of BTV and ITV in coexisting closely related species and how their individual traits differ under different drivers of ITV. We manipulated conditions in a greenhouse pot experiment with four common Carex species, where individuals of each species originated from four source localities. Individuals were grown in factorial combinations of two moisture levels, with and without a competitor (grass species Holcus lanatus, a frequent competitor). We analyzed the variability of six morphological traits on individuals in the greenhouse and three morphological traits in the source localities. Species identity was the main determinant of differences in most traits. Competition exerted a greater effect than water availability. For leaf dry matter content (LDMC) and vegetative height, competition's effect even exceeded the variability among species. On the contrary, for specific leaf area (SLA) and clonal spread, the interspecific differences exceeded ITV induced by experimental treatments. SLA measured in the greenhouse closely correlated with values measured in field populations, while LDMC did not. The variability caused by source locality of ramets in the greenhouse was small, although sometimes significant. Closely related species differ in their traits, but for some traits, ITV can exceed BTV. We can expect that ITV can modify the processes of community assembly, particularly among coexisting closely related species.
Keywords: functional traits; greenhouse experiment; intraspecific trait variability; closely related species; Carex species; competition; water availability; interspecific trait variability